2005
DOI: 10.1159/000089577
|View full text |Cite
|
Sign up to set email alerts
|

Sedative Drug Requirements during Flexible Bronchoscopy

Abstract: Background: There is a paucity of data comparing doses of sedative medication during bronchoscopy in immunosuppressed and non-immunosuppressed patients. Objectives: The aim of this study was to define the sedative medication doses used in specific patient groups during bronchoscopy. Methods: Bronchoscopy was performed under local anesthesia, sedation with intermittent boluses of intravenous midazolam and intravenous hydrocodone 5 mg. Two hundred and thirty-nine consecutive bronchoalveolar lavage procedures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…It is well known that patients with advanced oncological and haematological disease, including solid organ and bone marrow transplantation, intravenous drug users and HIV patients, have a higher incidence of complications during bronchoscopy [23]. Some patients with HIV infection require higher doses of sedation [6]. However, sedation requirements may depend on the anti-retrovirals being used and if they inhibit or augment the hepatic metabolism of propofol [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that patients with advanced oncological and haematological disease, including solid organ and bone marrow transplantation, intravenous drug users and HIV patients, have a higher incidence of complications during bronchoscopy [23]. Some patients with HIV infection require higher doses of sedation [6]. However, sedation requirements may depend on the anti-retrovirals being used and if they inhibit or augment the hepatic metabolism of propofol [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey of registered members of the British Thoracic Society, .95% of centres routinely perform sedated bronchoscopy [5]. Optimal sedation for flexible bronchoscopy has been assessed in a number of studies evaluating different sedative drug regimens using single agents or combinations thereof [6][7][8][9][10]. Propofol (2,6-di-isopropylphenol), a sedative hypnotic, has recently proved to be a safe and attractive alternative to combined sedation with midazolam and hydrocodone due to its rapid onset of action and fast recovery time, particularly if timely discharge was a priority [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of the present study, no specific trend was observed in the association between peak Pc,CO 2 and change in Pc,CO 2 with procedure duration, both a short and a longer procedure duration were associated with the peak Pc,CO 2 and change in Pc,CO 2 . The ability to effectively measure Pc,CO 2 is an important step in patient monitoring as diagnostic bronchoscopies are performed using routine sedation and also drugs, such as propofol, which are considered as general anaesthetics are being increasingly used also in the absence of a trained anaesthetist [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal sedation for flexible bronchoscopy has been assessed in a number of studies, which evaluated not only different sedative drug regimens but also particular drug requirements in specific sub-groups of patients [7][8][9][10]. In spite of the recommendations of the British Thoracic Society guidelines [1], combined sedation with opiate and a benzodiazepine has been shown to be effective and safe in a randomised, placebo-controlled trial, even in high-risk patients, such as those suffering from chronic obstructive pulmonary disease (COPD) [10].…”
mentioning
confidence: 99%